Closed spinal dysraphism in a 6-month-old mixed breed dog - Franco, Guilherme Galhardo; Martins De Siqueira, Emerson Goncalves [UNESP]; Leonel De Souza, Joao Augusto [UNESP]; De Castro Prado, Leonardo Oliveira [UNESP]; Rahal, Sheila Canevese [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Minto, Bruno Watanabe [UNESP]; Seullner Brandao, Claudia Valeria [UNESP]; Costa Junior, Jose Sergio [UNESP] (Czech Academy Agricultural Sciences, 2021)
The term spinal dysraphism defines an incomplete fusion or a bone defect that affects the neural structures of the spinal cord due to a neural tube malformation. A 6-month-old, male, mixed-breed dog, was evaluated for paraparesis, pelvic limb proprioceptive ataxia, faecal and urinary incontinence. A neurological examination indicated an L4-S3 spinal cord segment lesion. A thoracolumbar and lumbosacral spine magnetic resonance imaging was performed and a closed spinal dysraphism, with the presence of a lipomyelomeningocele, was detected. The magnetic resonance imaging showed an entire narrowing passage and a fibrous mass stemming from a wedge-shaped gap in the caudal region of the dorsal lamina of the L4 vertebra, leaving the spinal canal towards the skin surface in the region where the skin stigma was observed. A dorsal laminectomy was performed, the spinal cord was exposed, and the entire fibrous mass was excised. Three months postoperatively, the patient had a complete resolution of the urinary and faecal incontinence showing only a residual mild paraparesis, which remained six months after surgery. The surgical procedure resulted in the satisfactory recovery of the neurological signs.
Keywords: congenital malformation; lipomyelomeningocele; spina bifida